Hiring and the dynamics of the gender gap - Hannah Illing; Hanna Schwank; Linh T. Tô (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We investigate how the same hiring opportunity leads to different labor market outcomes for male and female full-time workers. To study firms' wage-setting behavior following exogenous vacancies, we analyze the wages of new hires after sudden worker deaths between 1981 and 2016. Using administrative data from Germany, we apply a novel technique to identify external replacement workers, and we use machine learning to compare replacements hired for comparable positions by similar firms. We find that female replacement workers' starting wages are, on average, 10 log points lower than those of replacing men of the same productivity. Differences in labor supply, within-firm adjustments, or outside options do not explain this gap; instead, we attribute it to gender differences in bargaining. We conclude that a significant portion of the gender wage gap emerges within firms at the hiring stage.
Keywords: J2; J31; J63; 330; Gender Wage Gap; Hiring; Labor Supply